Effect of natural aging on selected properties of wooden facade elements made of scots pine and chestnut - Topaloglu, Elif (Maderas. Ciencia y Tecnología, 2023)
Identifying wood species of each wood element of a historical wooden building and investigating the changes in wood properties due to exposed outdoors during its service life are important prerequisites for the maintenance and renovation of historical wooden buildings. In the present study, the changes in wood properties occurring during natural aging of two facade elements taken from a traditional house, which has a service life of approximately 100 years, were investigated. Destructive tests were used for the experiments. The wood species, moisture content, wood density, water absorption rate and chemical structure of both facade elements were determined. Microscopic analysis revealed that the molding was made from the wood of Scots pine (Pinus sylvestris) and the window jamb was made from chestnut (Castanea sativa). It was found that the cellulose and lignin on the outer surface of aged woods of both facade elements were degraded according to the FTIR analysis. The moisture and density values of aged wood for both facade elements were smaller than those of recent wood. The water absorption rates of aged woods of both molding and window jamb increased with natural aging.